Mutual learning with memory for semi-supervised pest detection - Zhou, Jiale; Huang, He; Sun, Youqiang; Chu, Jiqing; Zhang, Wei; Qu, Fang; Yang, Huamin (Frontiers in Plant Science, 2024)
Effectively monitoring pest-infested areas by computer vision is essential to precision agriculture in order to minimize yield losses and create early scientific preventative solutions. However, the scale variation, complex background and dense distribution of pests bring challenges to the accurate detection when utilizing vision technology. Simultaneously, supervised learning-based object detection heavily depends on abundant labeled data, which poses practical difficulties. To overcome these obstacles, in this paper, we put forward an innovative semi-supervised pest detection, PestTeacher. The framework that effectively mitigates the issues of confirmation bias and instability among detection results across different iterations. To address the issue of leakage caused by the weak features of pests, we propose the Spatial-aware Multi-Resolution Feature Extraction(SMFE) module. Furthermore, we introduce an Region Proposal Network(RPN) module with a cascading architecture. This module is specifically designed to generate higher quality anchors, which are crucial for accurate object detection. We evaluated the performance of our method on two datasets: the corn-borer dataset and the Pest24 dataset. The corn-borer dataset encompasses data from various corn growth cycles, while the Pest24 dataset is a largescale, multi-pest image dataset consisting of 24 classes and 25k images. Experimental results demonstrate that the enhanced model achieves about 80% effectiveness with only 20% of the training set supervised in both the corn-borer dataset and Pest24 dataset. Compared to the baseline model Soft Teacher, our model improves